Determination of Trace Metals in Individual Air Particulates Using Transmission Electron Microscopy - Ulrich, Sarah A. (My University, 2011)
Ultramafic rocks, primarily serpentinite, in northern California contain high levels of Cr and Ni, both of which are known carcinogens. Due to weathering and land usage practices, these serpentenites are transported into the highly populated Sacramento Valley. This research investigated the nature of Cr and Ni in airborne dust, as well as Zn, As, Pb and asbestos fibers. A 200kV transmission electron microscope (TEM) was used to analyze air filters supplied by the California Air Resources Board in order to determine the potential for the inhalation risk of Cr and Ni.
Color poster with text, charts, images, maps, and graphs.
Keywords: Trace elements--Health aspects; Ultrabasic rocks--California--Sacramento Valley; Transmission electron microscopy; Sacramento Valley (Calif.); Posters